Cultural Dialogue in West and East: In the World and the Novel - Alia Nikhat; Dr. Qazi Abdul RehmanAbid (Zaban-o-Adab, 2021)
Soon after the 9/11 the world changed its shape and the literature and the studies of literature also adopted new ways to understand contemporary World. After the influenced, books of S.P Huntington and Francis Focoyama the critics also evaluated the literature in this context. It was the new way of cultural studies or culture studies.In this article three Urdu novels have been studied and the result of this study is that many different cultures have a profound dialogue among each other. The cultures of colonizers and the colonized and the culture of apparently independent countries also influence and make meaning full dialogues.